Karthago, Tunesien: Grabung im Bereich der frühpunischen Häuser an der Rue Ibn Chabâat - Bolder-Boos, Marion; Baur, Christoph; Schön, Frerich; Willmitzer, Alice (e-Forschungsberichte des DAI, 2023)
At least three, possibly even four Early Punic houses have come to light at the Rue Ibn Chabâat site. They followed a north-south orientation and were from the start designed as courtyard houses with a central open area surrounded by rooms of different sizes. While over the course of time minor changes were made to the internal organisation of these housing units, the house plots as well as their orientation remained the same. At the end of the Early Punic period these houses were destroyed when a large building of presumably public character was erected here.